Proposal of a dedicated telemetry device for real-time and remote measurements - Pissolato Filho, José; Zanotto, André C.; Costa, Eduardo C. M.; Kurokawa, Sérgio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This work aims to demonstrate an application of telemetry for monitoring process variables. The authors developed the prototype of a dedicated device capable of multiplexing, encoding and transmitting real-time data signals via amplitude-shift keying modulation to remotely located device(s). The prototype development is described in details, enabling the reproduction of the proposed telemetry system for a three-phase motor as well as for other devices. Furthermore, the proposed device has an easy implementation by using of accessible components and low cost, also presenting a tutorial and educational purpose. © 2011 IEEE.
Keywords: amplitude-shift keying modulation; dedicated systems; multiplexing and encoding of data signals; RF circuits; switching power supplies; Telemetry of process variables; Amplitude shift keying; Dedicated systems; Low costs; Monitoring process; Prototype development; Real-time data; Remote measurement; RF-circuits; Telemetry systems; Three phase motor; Electric power supplies to apparatus; Encoding (symbols); Industrial electronics; Multiplexing; Power electronics; Real time systems; Real variables; Telemetering equipment